Fundamentals of applied statistics - Gupta, S. C.; Kapoor, V. K. (New Delhi: Sultan Chand & Sons, 2007)
This serves as a standard textbook for degree and post-graduate studies. The authors have successfully given a lucid exposition of different applications of statistics in Industry, Economics, Agriculture, Demography, Education and Psychology. Mathematical complexity is avoided. Elementary knowledge of mathematics (calculus) is enough to follow the book. Theory is suported by illustrations and problems. Many baffling problems are presented to make the reader self-reliant. Elaborate problems are given exercises at the end of each chapter, which infuse confidence.
Keywords: Analysis of variance; Statistical quality control; Vital statistics; Fertility